Conditional Cash Transfers: Do They Change Time Preferences and Educational Aspirations? - Diana Contreras Suarez; Lisa A. Cameron (Institute for the Study of Labor (IZA), 2016)
Conditional Cash Transfer programs are designed to increase human capital in poorer families. They do this directly through incentives and conditions. A further way these programs may influence household decisions is through impacts on preferences. Preferences may change as a result of new habit formation, information received through the program or by the relaxation of budget constraints which gives households a greater ability to look beyond their daily needs to plan for the future. Using a regression discontinuity design we test whether a large CCT program in Colombia affects the time preferences of participating households and aspirations for their children's education. We find that it does not. Thus, the positive impacts identified in previous studies appear to be driven by the ongoing receipt of the cash transfers and the associated conditions. Hence if the transfers were to stop, program benefits would likely be limited to those obtained during the program.
Keywords: O15; I25; I38; D91; 330; conditional cash transfers; time preferences; educational aspirations; regression discontinuity design; Colombia